ALASAN PERALIHAN WALI NASAB KEPADA WALI HAKIM DALAM PELAKSANAN PERKAWINAN PERSPEKTIF HUKUM ISLAM DI KANTOR URUSAN AGAMA KECAMATAN NGUTER KABUPATEN SUKOHARJO TAHUN 2022-2023 - Rohmana, Indah Amin; Syamsuddin, S; Baehaqi, B (AL HUKMU: Journal of Islamic Law and Economics, 2024)
The research results of the reasons for the transition of the nasab guardian to the judge's guardian at the KUA Nguter Kec. are as follows 1) There is no nasab guardian 2) Wali Nasabnya Adhal 3) The Nasab Wali has no news anymore. 4) The Nasab Wali is Non-Muslim. The procedure for transferring the nasab guardian to the judge's guardian at the KUA Nguter Kecamatan as follows 1) Make a letter to RT / RW 2) Take care of the local KUA letter. 3) Fill out forms N1, N2, N3 and N4 4) Collect the marriage certificate of both parents. 5) Collect personal data of both bride and groom. 6) Submit a divorce certificate for catin widower / widow. 7) Collect 3x4 and 4x6 blue bacground photos. 8) Collect photocopies of witness ID cards. 9) Fill in the letter of ugeran wali hakim. 10) If the guardian is reluctant to marry the catin, attach a letter of application for the determination of wali adhal from the religious court